Prognostic factors on trabeculectomy among glaucoma patients in Kelantan - Isa, Khairul Anuar Md (2008)
Introduction: The study on trabeculectomy success rate in Malaysian population was relatively scarce. Information on trabeculectomy success rate and prognostic factors for trabeculectomy outcome is needed to help ophthalmologist to determine the prognosis and search for better way to increase success rate of trabeculectomy. Objectives: To detennine the five year trabeculectomy success rate and to identify the prognostic factors that may influence the trabeculectomy outcome among glaucoma patients treated at HUSM. Methodology: A retrospective record review study was conducted involving 96 glaucoma patients (96 eyes) who undetwent trabeculectomy from 1·S I January 1990 to 31st July 2006. Additional follow-up of one year after the recruitment of the study subjects was done from 151 August 2006to31 si July 2007. All patients who fulfilled the selection criteria were included in the study. The medical records were reviewed by a single researcher with the help of senior consultant of ophthalmology and important information on the variables of interest and trabeculectomy outcome status were collected and recorded into a clinical form . The Kaplan Meier and Cox Proportional Hazards regression analysis was used in statistical analysis. Results: The median trabeculectomy success time was 18.8 months and the overall trabeculectomy success rate was 36. l % (95% CI: 25.6, 46.8) at five year. Based on the Cox's regression analysis after adjusting other va1iables, the significant prognostic factors that may influence trabeculectomy outcome was history of previous ocular surgery (HR=2.31, 95% Cl: 1.21, 4.41; p=0.019). Conclusion: Trabeculectomy success rate for glaucoma patients at HUSM was acceptably low. The history of previous ocular surgery was identified as the only significant prognostic factor for trabeculectomy failure. Better post trabeculectomy management for glaucoma patient that had undergone previous ocular surgery is recommended to obtain higher trabeculectomy success rate in those patient.